Mauritius : Assessment Letter in the Context of the Aid for Trade Initiative. (Policy Papers; Policy Paper ;, 2006)
This note presents the IMF staff's assessment of recent macroeconomic developments in Mauritius and the authorities' reform strategy to address the negative impact of the loss of preferential access for the textile and sugar sectors and to raise potential growth. Drawing on the findings of an IMF staff visit to Mauritius in August 2006, it also updates the most recent staff report on the 2005 Article IV consultation discussed by the Executive Board on December 2, 2005 (published as Country Report No. 06/209.